Penilaian pembelajaran pada Guru SD di Kabupaten Bone - Nurfaizah AP (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The success of the assessment process is highlydependent on the teacher, but the reality in the field shows thatteachers still have difficulties in preparing assessment plans,conducting assessments, processing assessments and utilizingassessment results. To date, most elementary school teachersin Patimpeng District, Bone Regency, especially teachers whoteach in Paccing and Massila Villages tend to still measure thestudents' ability using the Lower Order Thinking Skillsand the questions that are made are not contextual. This PKMaimed to provide training in developing skills of assessmentinstructional items and its assessment rubric for elementaryteacher groups in Bone Regency. The program usedparticipatory, group and individual approaches. The methodcovered the lecture, discussion/Forum Group Discussion andproject. The partner groups consisted of 2 groups. Theseactivities included: 1) Training and direct practice to formulateassessment indicators, 2) Determine the appropriate assessmenttechniques in accordance with the basic competenciestaught, 3) Develop items of High-Level Thinking assessmentinstruments and their assessment rubrics. The results of thisactivity were: 1) The elementary teacher group was able toformulate assessment indicators, 2) The teachers were able toprocess and describe the results of the assessment of attitudes,knowledge and skills, 3) The teachers developed items ofHigh-Level Thinking assessment instruments as well as theassessment rubrics.